Zagadnienie Kościoła w kontekście ascetycznym u Marka Eremity - Grzywaczewski, Józef (Collectanea Theologica, 2019)
Mark the Ascetic (called also in English Mark the Heremit) represents the monastic milieu of the fifth century. He wrote about the Church while discussing other questions. He clearly distinguished heterodox groups and the Catholic Church. He refuted the theories of the Melchizedekians, Adoptionists, Messalians, Arians and Apollinarians, but especially Nestorians. Mark considered heretics as people in error and as those who have broken fidelity to their baptism. He underlined that his own teaching was conformed to the Christian tradition. In his works, similar points with the teaching of earlier Christian writers, such as Basil of Caesarea, John Chrysostom, Evagrius Ponticus, Cyril of Alexandria and Gregory of Nazianzus, should be noticed. Mark presented the Church as a place of sanctification for lay people and monks. He proclaimed Christ as God’s Son and as the true Man, not only a creature having a human body. He highlighted the importance of the sacraments of baptism and the Eucharist. In Mark’s works, we see Saint Peter and Saint Paul as good teachers of the divine truth, who gave an example of the Christian virtues, but there are no references to the position of the Church of Rome in Christianity. The works of Mark the Ascetic were popular in late antiquity, especially in the East; they were translated into several languages. In the West, they were used especially in the time of controversies between the Catholics and the Protestants.